2008
DOI: 10.1149/1.2939212
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Ultrahigh Resolution Microstructural Studies for Understanding Localized Corrosion Behavior of Al Alloys

Abstract: The corrosion behavior of different tempers of two aluminum alloys, AA7050 and an experimental Al-Mg-Cu-Si alloy, was studied in NaCl solution by anodic polarization and scanning electron microscopy and was correlated with differences in the microstructure. Potentiodynamic polarization experiments were performed on samples from the exact sheets used by others to study the microstructure evolution during the early stages of the precipitation sequence by high-resolution characterization tools ͓i.e., high-resolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…It has been suggested previously that the samples exhibiting surface layer dissolution were very susceptible to crevice corrosion under the edge of the mask, because the active surface layer extended on the surface beneath the lacquer mask. 11,13 There were some evidences of metastable pitting in this potential range, as indicated by small hydrogen bubbles at specific spots on the surface. However, most of the hydrogen bubbles accumulated at the edge of the mask from crevice activity.…”
Section: Resultsmentioning
confidence: 96%
“…It has been suggested previously that the samples exhibiting surface layer dissolution were very susceptible to crevice corrosion under the edge of the mask, because the active surface layer extended on the surface beneath the lacquer mask. 11,13 There were some evidences of metastable pitting in this potential range, as indicated by small hydrogen bubbles at specific spots on the surface. However, most of the hydrogen bubbles accumulated at the edge of the mask from crevice activity.…”
Section: Resultsmentioning
confidence: 96%
“…Breakdown behavior similar to that of AA7055 in the present study was reported previously for AA7075 30 and AA 7050. 33 The E P increased from the under-aged to peak-aged tempers because of the decrease in the Zn content in the matrix. 32,33 The E P decreased from the peak-aged to over-aged tempers due to the depletion of Cu in the matrix solid solution.…”
Section: Resultsmentioning
confidence: 99%
“…33 The E P increased from the under-aged to peak-aged tempers because of the decrease in the Zn content in the matrix. 32,33 The E P decreased from the peak-aged to over-aged tempers due to the depletion of Cu in the matrix solid solution. 27,34 The effect of changes in the matrix Zn content dominated the effect of changes in the matrix Cu content during under-aging, while the opposite trend behaved during over-aging.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations